1996
DOI: 10.1007/bf00702335
|View full text |Cite
|
Sign up to set email alerts
|

Benzyl-N-acetyl-α-d-galactosaminide inhibits the sialylation and the secretion of mucins by a mucin secreting HT-29 cell subpopulation

Abstract: We have analysed the mucins synthesized by the HT-29 MTX cell subpopulation, derived from the HT-29 human colon carcinoma cells through a selective pressure with methotrexate (Lesuffleur et al., 1990, Cancer Res 50: 6334-43), in the presence of benzyl-N-acetyl-alpha-galactosaminide (GalNAc alpha-O-benzyl), which is a potential competitive inhibitor of the beta 1,3-galactosyltransferase that synthesizes the T-antigen. The main observation was a 13-fold decrease in the sialic acid content of mucins after 24 h of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
53
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 28 publications
2
53
0
Order By: Relevance
“…However, unmyristoylated annexin XIIIb was not bound to the membrane but exclusively present in the cytosolic fraction (50). Beyond the requirement of the myristoyl moiety for mem-brane binding (50), our data suggest that in HT-29 5M12 cells, the association of membrane-bound annexin XIIIb with lipid microdomains involves its interaction with sialylated epitopes, as we showed that GalNAc␣-O-bn inhibits sialylation of glycoproteins and likely glycolipids by the two sialyltransferases ST3Gal I and ST3Gal IV (22,23).…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…However, unmyristoylated annexin XIIIb was not bound to the membrane but exclusively present in the cytosolic fraction (50). Beyond the requirement of the myristoyl moiety for mem-brane binding (50), our data suggest that in HT-29 5M12 cells, the association of membrane-bound annexin XIIIb with lipid microdomains involves its interaction with sialylated epitopes, as we showed that GalNAc␣-O-bn inhibits sialylation of glycoproteins and likely glycolipids by the two sialyltransferases ST3Gal I and ST3Gal IV (22,23).…”
Section: Discussionmentioning
confidence: 57%
“…In this cell line, GalNAc␣-O-bn was found to inhibit primarily the terminal sialylation by the sialyltransferases ST3Gal I and ST3Gal IV, and we suggested that sialylation of apical glycoproteins may act as a targeting signal for apical delivery (19,22,23). The goal of this work was to examine the anterograde traffic in cloned HT-29 5M12 cells material of GalNAc␣-O-bn-treated cells shifted in fraction 2 of lower buoyant density.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This effect was shown to be cell-specific and connected to the inhibition of the sialylation of mucins by ST3Gal I, a glycosyltransferase highly expressed in HT-29 cells. 50,52 Here, we observed a specific inhibition in the localization of MUC1 and MUC5AC at the surface of GalNAc␣-O-bn treated HT-29 5M21 cells cultured on collagen, whereas the localization of E-cadherin was not affected. This observation showed that the gain of Ecadherin function in GalNAc␣-O-bn treated HT-29 5M21 cells could not be simply attributed to an inhibition of the glycosylation of mucins but to a more complex mechanism resulting in the loss of expression of MUC1 and MUC5AC at the periphery of the cell.…”
Section: Immunofluorescence Analysis Of the Distribution Of E-cadherimentioning
confidence: 66%
“…Previous studies have suggested that O-glycans may influence protein stability, as is thought to be the case in the human disease, familial tumoral calcinosis (26,(31)(32). Other studies in cell culture using chemical inhibitors of O-glycan extension have demonstrated that alterations in O-glycan formation can affect secretion and trafficking of certain proteins (33)(34)(35)(36). However, these inhibitors also affect other glycosylation pathways, making specific conclusions about the role of mucin-type O-glycans difficult.…”
mentioning
confidence: 98%